Growing Industrial Clusters in Asia : Serendipity and Science - Yusuf, Shahid (Washington, DC : World Bank, 2012)
Can clusters be made to order? By Shahid Yusuf. Lessons from the development of silicon valley and its entrepreneurial support network for Japan by Martin Kenney. The emergence of Hsinchu science park as an IT cluster by Tain-Jy Chen. Coping with globalization of production networks and digital convergence: the challenge of ICT cluster development in Singapore by Poh-Kam Wong. Bangalore cluster: evolution, growth, and challenges by Rakesh Basant. ICT clusters and industrial restructuring in the Republic of Korea: the case of Seoul by Sam Ock Park. Constructing jurisdictional advantage in a mature economy: the case of Kitakyushu, Japan by Maryann P. Feldman. Kitakyushu: desperately seeking clusters by Kaoru Nabeshima and Shoichi Yamashita.